2009
DOI: 10.1590/s0102-09352009000400026
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation for large data sets by random regression models in Nellore cattle

Abstract: Expected progeny differences (EPD) of Nellore cattle estimated by random regression model (RRM) and multiple trait model (MTM) were compared. Genetic evaluation data included 3,819,895 records of up nine sequential weights of 963,227 animals measured at ages ranging from one day (birth weight) to 733 days. Traits considered were weights at birth, ten to 110-day old, 102 to 202-day old, 193 to 293-day old, 283 to 383-day old, 376 to 476-day old, 551 to 651-day old, and 633 to 733-day old. Seven data samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Several studies in beef cattle have demonstrated the importance of including maternal effects in the analysis (Meyer et al, 1993;Baldi et al, 2010b;Nobre et al, 2009;Menezes, 2010). Meyer (1997) reported that the models that rule out maternal effects lead to overestimates of direct heritability.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in beef cattle have demonstrated the importance of including maternal effects in the analysis (Meyer et al, 1993;Baldi et al, 2010b;Nobre et al, 2009;Menezes, 2010). Meyer (1997) reported that the models that rule out maternal effects lead to overestimates of direct heritability.…”
Section: Resultsmentioning
confidence: 99%